การสอบเทียบระบบกลไกแขนกลแบบขนาน - เอกพจน์ สุนทรมาตฤก (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
This research covers the calibration method of a 6-DOF parallel mechanism manipulator arm. The calibration process is done in order to improve the accuracy of this arm which typically used as a master arm for rapid prototyping process in manufactured type of process. In this research, the level-2 calibration, covering only the errors of the physical of mechanism such as link, joint, etc, are considered. In general, two mathematics models, kinematics and Jacobian, were concerned in order to obtain the related parameters of the mechanism. With respect to the external calibration devices, the forward kinematics is more appropriate to be used. A calibration object which is an external device developed in this work, consists of many known fixed referenced points, is used in the calibration process. The errors between the known referenced points and the measurement using the robot arm are recorded. The parameters in the manipulator arm are analyzed and adjusted until the best results, based on minimizing of the least square error, are presented. In this research, the number of parameters that provide suitable result is found. The most suitable set of parameter consists of 51 parameters. According to the test on 16 reference points, the accuracy of the master arm is better than 1 mm. However, to increase the number of the parameters, the accuracy could not be improved because some errors are existed. These errors deal with some uncertainties, for example the clearance in bearings and improper measurements using CMM. Because, the force exerted, during measurements using CMM, lead to some deformation and error. Some statistical method may be needed to improve the accuracy in the measurement.